Tenecteplase Efficacy in Patients With Distal Occlusions: Secondary Analysis of the TASTE Randomized Clinical Trial - Vignan Yogendrakumar; Justin Phung; Hannah T. Johns; Leonid Churilov; Carlos Garcia-Esperon; Gagan Sharma; Niruta Dhimal; Chushuang Chen; Longting Lin; Beng Lim Chew; Felix C. Ng; Akshay Deepak; et al. (Stroke, 2026)
BACKGROUND: Tenecteplase has been previously evaluated in large- and medium-sized vessel occlusion subgroups, but its effectiveness in more distal occlusions, particularly those involving the distal middle cerebral artery branches or the anterior cerebral artery and posterior cerebral artery territories, and across varying ischemic core and perfusion profiles, remains uncertain. METHODS: We performed a secondary analysis of TASTE (Tenecteplase Versus Alteplase for Stroke Thrombolysis Evaluation), a randomized clinical trial comparing tenecteplase and alteplase in patients presenting within 4.5 hours of symptom onset with perfusion imaging-confirmed stroke and evidence of target mismatch (penumbra/core ratio >1.8 and an absolute difference >15 mL). The primary outcome was the modified Rankin Scale (mRS) score of 0 to 1 at 90 days. We compared the effect of tenecteplase versus alteplase in subgroups based on occlusion site (proximal M2, distal M2, M3 and beyond, anterior cerebral artery, and posterior cerebral artery), ischemic core, core growth rate, and penumbra. The treatment effect of tenecteplase and alteplase was compared stratifying by the subgroup of interest, adjusting for age, baseline National Institutes of Health Stroke Scale score, and premorbid mRS score in modified Poisson regression models. RESULTS: Of the 680 patients enrolled, 492 were included in the primary analysis (median age, 73 [interquartile range, 63–82] years; male sex: 306/492 [62%]). Two hundred forty-two (49%) received tenecteplase, and 250 (51%) received alteplase. Tenecteplase was associated with a higher proportion of mRS score of 0 to 1 with distal (M3 and beyond) occlusions (tenecteplase: 62/81 [77%] versus alteplase: 59/93 [63%]; adjusted risk ratio, 1.23 [95% CI, 1.04–1.46]). Numerically higher rates of mRS score of 0 to 1 were observed with distal M2 (tenecteplase: 30/46 [65%] versus alteplase 28/48 [58%]; adjusted risk ratio, 1.14 [95% CI, 0.84–1.54]) and anterior cerebral artery occlusions (tenecteplase: 12/21 [57%] versus alteplase 5/13 [38%]; adjusted risk ratio, 1.46 [95% CI, 0.71–3.00]). No treatment differences were seen for proximal M2 or posterior cerebral artery occlusions ( P interaction across all occlusion sites: 0.89). Across ischemic core, penumbra, and core growth rate subgroups, no difference in treatment effect was observed. CONCLUSIONS: Patients with distal middle cerebral artery occlusions who are treated with tenecteplase are more likely to achieve an mRS score of 0 to 1 at 90 days than those treated with alteplase. REGISTRATION: URL: https://www.anzctr.org.au ; Unique identifier: ACTRN12613000243718.